Exploring The Role Of Teacher Leaders In The Implementation Of The Independent Curriculum - Nur Hakim; Ari Susetiyo; Riska Latifatul Husna (Celebes Journal of Elementary Education, 2026)
The implementation of the Merdeka curriculum at several educational institutions continues to encounter various challenges. These include teachers focusing solely on instruction without sufficiently addressing students' overall development, a limited understanding of the Merdeka curriculum concept, continued dependence on traditional teaching methods, minimal use of information technology, and difficulties in applying differentiated learning strategies. In this context, having a teacher leader is crucial as both an instructional leader and a change agent dedicated to advancing educational reform. SD Negeri 2 Kampungbaru is among the schools actively implementing the Merdeka curriculum, where the teacher leader plays a central role in driving change. This study investigates: (1) the role of the teacher leader in implementing the Merdeka curriculum at SD Negeri 2 Kampungbaru, and (2) how their role is evaluated during the process. Employing a qualitative descriptive approach, data was gathered through observations, interviews, and documentation. Participants included the principal, homeroom teachers, students, and the teacher leader directly involved in curriculum implementation. Data analysis consisted of three steps: data reduction, data display, and conclusion drawing, providing a comprehensive understanding of participants’ experiences. Results show that the teacher leader at SD Negeri 2 Kampungbaru fulfills five main roles: instructional leader, learning community facilitator, teacher mentor, discussion and collaboration facilitator, and student leadership developer. Feedback from the principal, teachers, students, and the teacher leader indicates these roles are effectively performed, leading to enhanced learning quality, stronger character development among students, and increased collaboration within the school.